Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the inverse of a matrix [tex]\( Y \)[/tex], we need to check whether the determinant of [tex]\( Y \)[/tex] is non-zero. If the determinant is zero, the matrix does not have an inverse. If the determinant is non-zero, we can find the inverse using the formula for the inverse of a 2x2 matrix:
[tex]\[ Y^{-1} = \frac{1}{\text{det}(Y)} \begin{bmatrix} d & -b \\ -c & a \end{bmatrix} \][/tex]
where [tex]\( Y = \begin{bmatrix} a & b \\ c & d \end{bmatrix} \)[/tex] and [tex]\(\text{det}(Y) = ad - bc \)[/tex].
Let's find the inverses for each matrix given.
### 1. [tex]\( Y = \begin{bmatrix} 2 & -2 \\ -1 & 2 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 2 - (-2) \cdot (-1) = 4 - 2 = 2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{2} \begin{bmatrix} 2 & 2 \\ 1 & 2 \end{bmatrix} = \begin{bmatrix} 1 & 1 \\ 0.5 & 1 \end{bmatrix} \][/tex]
### 2. [tex]\( Y = \begin{bmatrix} 1 & -1 \\ 1 & 1 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 1 - (-1) \cdot 1 = 1 + 1 = 2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{2} \begin{bmatrix} 1 & 1 \\ -1 & 1 \end{bmatrix} = \begin{bmatrix} 0.5 & 0.5 \\ -0.5 & 0.5 \end{bmatrix} \][/tex]
### 3. [tex]\( Y = \begin{bmatrix} 2 & -1 \\ 1 & 0 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 0 - (-1) \cdot 1 = 0 + 1 = 1 \)[/tex].
[tex]\[ Y^{-1} = \begin{bmatrix} 0 & 1 \\ -1 & 2 \end{bmatrix} \][/tex]
### 4. [tex]\( Y = \begin{bmatrix} 2 & 3 \\ 1 & 1 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 1 - 3 \cdot 1 = 2 - 3 = -1 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-1} \begin{bmatrix} 1 & -3 \\ -1 & 2 \end{bmatrix} = \begin{bmatrix} -1 & 3 \\ 1 & -2 \end{bmatrix} \][/tex]
### 5. [tex]\( Y = \begin{bmatrix} 1 & 4 \\ 1 & 3 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 3 - 4 \cdot 1 = 3 - 4 = -1 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-1} \begin{bmatrix} 3 & -4 \\ -1 & 1 \end{bmatrix} = \begin{bmatrix} -3 & 4 \\ 1 & -1 \end{bmatrix} \][/tex]
### 6. [tex]\( Y = \begin{bmatrix} 1 & 2 \\ 3 & 4 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 4 - 2 \cdot 3 = 4 - 6 = -2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-2} \begin{bmatrix} 4 & -2 \\ -3 & 1 \end{bmatrix} = \begin{bmatrix} -2 & 1 \\ 1.5 & -0.5 \end{bmatrix} \][/tex]
### 7. [tex]\( Y = \begin{bmatrix} 3 & 4 \\ 3 & 4 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 3 \cdot 4 - 4 \cdot 3 = 12 - 12 = 0 \)[/tex].
This matrix does not have an inverse because the determinant is zero, indicating that the matrix is singular.
Therefore, the inverse matrices are as follows:
1. [tex]\( Y_1^{-1} = \begin{bmatrix} 1 & 1 \\ 0.5 & 1 \end{bmatrix} \)[/tex]
2. [tex]\( Y_2^{-1} = \begin{bmatrix} 0.5 & 0.5 \\ -0.5 & 0.5 \end{bmatrix} \)[/tex]
3. [tex]\( Y_3^{-1} = \begin{bmatrix} 0 & 1 \\ -1 & 2 \end{bmatrix} \)[/tex]
4. [tex]\( Y_4^{-1} = \begin{bmatrix} -1 & 3 \\ 1 & -2 \end{bmatrix} \)[/tex]
5. [tex]\( Y_5^{-1} = \begin{bmatrix} -3 & 4 \\ 1 & -1 \end{bmatrix} \)[/tex]
6. [tex]\( Y_6^{-1} = \begin{bmatrix} -2 & 1 \\ 1.5 & -0.5 \end{bmatrix} \)[/tex]
7. [tex]\( Y_7^{-1} = \text{no inverse (determinant is zero)} \)[/tex]
[tex]\[ Y^{-1} = \frac{1}{\text{det}(Y)} \begin{bmatrix} d & -b \\ -c & a \end{bmatrix} \][/tex]
where [tex]\( Y = \begin{bmatrix} a & b \\ c & d \end{bmatrix} \)[/tex] and [tex]\(\text{det}(Y) = ad - bc \)[/tex].
Let's find the inverses for each matrix given.
### 1. [tex]\( Y = \begin{bmatrix} 2 & -2 \\ -1 & 2 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 2 - (-2) \cdot (-1) = 4 - 2 = 2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{2} \begin{bmatrix} 2 & 2 \\ 1 & 2 \end{bmatrix} = \begin{bmatrix} 1 & 1 \\ 0.5 & 1 \end{bmatrix} \][/tex]
### 2. [tex]\( Y = \begin{bmatrix} 1 & -1 \\ 1 & 1 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 1 - (-1) \cdot 1 = 1 + 1 = 2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{2} \begin{bmatrix} 1 & 1 \\ -1 & 1 \end{bmatrix} = \begin{bmatrix} 0.5 & 0.5 \\ -0.5 & 0.5 \end{bmatrix} \][/tex]
### 3. [tex]\( Y = \begin{bmatrix} 2 & -1 \\ 1 & 0 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 0 - (-1) \cdot 1 = 0 + 1 = 1 \)[/tex].
[tex]\[ Y^{-1} = \begin{bmatrix} 0 & 1 \\ -1 & 2 \end{bmatrix} \][/tex]
### 4. [tex]\( Y = \begin{bmatrix} 2 & 3 \\ 1 & 1 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 2 \cdot 1 - 3 \cdot 1 = 2 - 3 = -1 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-1} \begin{bmatrix} 1 & -3 \\ -1 & 2 \end{bmatrix} = \begin{bmatrix} -1 & 3 \\ 1 & -2 \end{bmatrix} \][/tex]
### 5. [tex]\( Y = \begin{bmatrix} 1 & 4 \\ 1 & 3 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 3 - 4 \cdot 1 = 3 - 4 = -1 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-1} \begin{bmatrix} 3 & -4 \\ -1 & 1 \end{bmatrix} = \begin{bmatrix} -3 & 4 \\ 1 & -1 \end{bmatrix} \][/tex]
### 6. [tex]\( Y = \begin{bmatrix} 1 & 2 \\ 3 & 4 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 1 \cdot 4 - 2 \cdot 3 = 4 - 6 = -2 \)[/tex].
[tex]\[ Y^{-1} = \frac{1}{-2} \begin{bmatrix} 4 & -2 \\ -3 & 1 \end{bmatrix} = \begin{bmatrix} -2 & 1 \\ 1.5 & -0.5 \end{bmatrix} \][/tex]
### 7. [tex]\( Y = \begin{bmatrix} 3 & 4 \\ 3 & 4 \end{bmatrix} \)[/tex]
Determinant [tex]\( \text{det}(Y) = 3 \cdot 4 - 4 \cdot 3 = 12 - 12 = 0 \)[/tex].
This matrix does not have an inverse because the determinant is zero, indicating that the matrix is singular.
Therefore, the inverse matrices are as follows:
1. [tex]\( Y_1^{-1} = \begin{bmatrix} 1 & 1 \\ 0.5 & 1 \end{bmatrix} \)[/tex]
2. [tex]\( Y_2^{-1} = \begin{bmatrix} 0.5 & 0.5 \\ -0.5 & 0.5 \end{bmatrix} \)[/tex]
3. [tex]\( Y_3^{-1} = \begin{bmatrix} 0 & 1 \\ -1 & 2 \end{bmatrix} \)[/tex]
4. [tex]\( Y_4^{-1} = \begin{bmatrix} -1 & 3 \\ 1 & -2 \end{bmatrix} \)[/tex]
5. [tex]\( Y_5^{-1} = \begin{bmatrix} -3 & 4 \\ 1 & -1 \end{bmatrix} \)[/tex]
6. [tex]\( Y_6^{-1} = \begin{bmatrix} -2 & 1 \\ 1.5 & -0.5 \end{bmatrix} \)[/tex]
7. [tex]\( Y_7^{-1} = \text{no inverse (determinant is zero)} \)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.